Corporate Governance In Palm Oil Companies In Aceh Province - Safrina Safrina; Khairani Khairani (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2020)
Nowadays, companies are not only required to provide information on financial accountability but also about corporate performance related to social and environmental aspects in order to promote shareholder values and sustainable practices, which eventually lead to the concept of corporate governance. This study aims to discuss the implementation of corporate governance, in palm oil companies in Aceh Province. A qualitative research method is applied with an empirical juridical approach. Data were collected by interviewing respondents and analyzing corporate reports. The result found that the implementation of corporate governence by the companies through the availability of code of good corporate governance (GCG) and code of conduct. Although it does not necessarily guarantee the implementation applied properly, but it can show company commitment to run a good business. Some companies also implement corporate social and environmental responsibility in a different approach. However, some of the activities are actually not in accordance with existing regulations, but is only limited to activities that have no direct impact on community.